Amyotrophic lateral sclerosis causes small fiber pathology. (February 2016) - Dalla Bella, E.; Lombardi, R.; Porretta‐Serapiglia, C.; Ciano, C.; Gellera, C.; Pensato, V.; Cazzato, D.; Lauria, G.
Abstract : Background and purpose: Our aim was to address the correlation between small fiber loss and amyotrophic lateral sclerosis (ALS) for disease onset, phenotype, genotype, duration, severity and sensory findings. Methods: Consecutive patients referred for suspected ALS were screened. Exclusion criteria were possible ALS and previous diagnosis or known risk factors for small fiber neuropathies. A sural nerve conduction study (NCS) was bilaterally recorded. The ALS functional rating scale revised was administered and loss of functions were calculated using the Milano−Torino staging (MITOS) system. Sensory symptoms and signs were recorded. Genetic analysis was performed by the next‐generation sequencing approach. Skin biopsy was performed at the distal leg and intraepidermal nerve fiber (IENF) density was quantified in three non‐consecutive sections following published guidelines. Findings were referred to age‐ and sex‐adjusted normative values. Results: Fifty‐seven patients including six with facial onset sensory and motor neuronopathy (FOSMN) were enrolled. Eight (15.7%) pure ALS patients and five (83%) FOSMN patients complained of sensory disturbances with different distributions. Sural NCS was normal in all except two patients. IENF density was reduced in 75.4% of pure ALS and 50% of FOSMN patients, without correlation with any disease features. IENF density was similarly reduced in bulbar (78.5%), flail limb (87.5%), pyramidal (100%), and spinal (68.2%) onset, as well as in genetic (83.3%) and sporadic (82%) ALS. There was no correlation with genotype, disease duration and severity. Conclusions: Intraepidermal nerve fiber loss is a feature of most ALS patients. It does not correlate with onset, phenotype, course and severity of the disease, and cannot be considered a clinical or prognostic biomarker.